Paleoseismological investigation of the eastern "segment" of the Heliki fault, Gulf of Corinth, Greece - ΠΑΥΛΙΔΗΣ, Σ.; ΚΟΥΚΟΥΒΕΛΑΣ, Ι.; ΣΤΑΜΑΤΟΠΟΥΛΟΣ, Λ.; ΑΓΡΑΦΙΩΤΗΣ, Δ.; ΑΛΕΞΑΝΔΡΗΣ, Γ. Α.; ΖΥΓΟΥΡΗ, Β.; ΣΜΠΟΡΑΣ, Σ. (Bulletin of the Geological Society of Greece, 2001)
Paleoseismological analysis based on geological data enable us to understand the recent seismic history of the Eliki fault. Along the eastern "segment (or strand)" scarp 5 trenches have been excavated (8x5x2m), their walls were mapped in scale 1:20 and further analyzed by precise tectono-stratigraphic methodology. The Kerynitis river, which crosses the Eliki fault from S to Ν and supplies the alluvial plain, has subsided at a rate of 1.4 mm/ yr. The river was running from west to east, resulting the fluvial conglomerates in the trenches, which have buried under the colluvial sediments. Based on colluvium stratigraphy, displacement of distinct horizons, deposition of sedimentary layers and C14 dating, faulting events have been identified affecting unconsolidated sediments in the trench. The penultimate 373 BC event and the two younger events with a throw of 0.93 m and 1.37 m respectively, the third event, with a throw of 0.44 m, suggest a variable seismic history.